2021
DOI: 10.1007/s40519-021-01228-y
|View full text |Cite
|
Sign up to set email alerts
|

Orthorexia Nervosa and its association with obsessive–compulsive disorder symptoms: initial cross-cultural comparison between Polish and Italian university students

Abstract: There is limited evidence of a link between Orthorexia Nervosa (ON) and Obsessive–Compulsive Disorder (OCD), and no definitive conclusions can be drawn. The interplay between socio-cultural context and ON has been poorly investigated as well. Therefore, the objectives of the present study were: (1) to investigate the differences in ON and OCD symptoms and (2) to assess the relationship between ON and OCD symptoms among university students. Six hundred and sixty-six university students participated in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…The current study is a part of a project about maladaptive eating in adulthood from a cross-cultural perspective (MEALS study). The procedure of the study has been described in detail in the previous work [ 31 ]. To sum up, the administration session took place in one session based on a series of self-report questionnaires that participants had to fill out via Google Forms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study is a part of a project about maladaptive eating in adulthood from a cross-cultural perspective (MEALS study). The procedure of the study has been described in detail in the previous work [ 31 ]. To sum up, the administration session took place in one session based on a series of self-report questionnaires that participants had to fill out via Google Forms.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study [ 24 ] demonstrated that higher overweight preoccupation, higher appearance orientation and the presence of an eating disorder history (the strongest predictor) were predictors of ON among Australian university students. Another study [ 3 ] showed that pathological eating, eating style, Mediterranean diet, compulsive symptoms, and subjective social status predicted ON among German young adults, whereas weight control, emotion regulation, low sensorial appeal, and younger age predicted ON among Spanish university students [ 31 ]. The objective of the present study was to assess whether disordered eating attitudes, self-esteem, and physical activity are associated with ON in young adults (from Poland and Italy).…”
Section: Introductionmentioning
confidence: 99%
“…However, it was higher than some observed with other sub-scores of ORTO test (Table 4 ). This finding suggests that, among the limitations, we did not include the OCD in the “exclusion diagnosis”[ 50 ]. However, Łucka et al [ 29 ] using ORTO-15 (score of 35 was considered as cut-off point), EAT-26 and Maudsley Obsessive Compulsive Inventory (MOCI), found that individuals with suspected ON (ORTO-15, score of 35) had higher BMI and EAT-26 score, whereas MOCI did not differ from ORTO-15 negative group.…”
Section: Discussionmentioning
confidence: 99%
“…Although a generalization to the whole population should not be made, considering the recent suggestions on the need for further investigation of the comorbidity between ON and OCD across different cultural groups[ 50 ], it emerged that ON could be an indicator/symptom of other problems related to body image perception, as well as high PA, psychological distress, appearance, fitness, health, or IO, in some university students. Accordingly, recent studies have found relationships between ON, vigorous-intensity PA and dieting[ 47 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…People with ON have been described as having excessively high demands on themselves, along with a strong sense of harsh criticism towards themselves and those around them, and a strong obsession with eliminating the elements of their personality that they perceive as defects [2,8]. Cross-cultural aspects seem to modify the association between perfectionism and ON, as evidenced by a recent Polish-Italian study on university students [51]. Interestingly, from a methodological point of view, the ability to document an association between OCD and ON involves the questionnaire implemented; a multi-center, observational, controlled study showed that the revised version of ORTO-15, namely ORTO-R, overcomes difficulties of ORTO-15 in detecting the aforementioned association [34].…”
Section: Mental Health-related and Nutritional Correlates Of Onmentioning
confidence: 99%